1962
DOI: 10.1152/ajplegacy.1962.202.6.1098
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydration on renal function and medullary sodium during vasopressin infusion

Abstract: Mild and severe degrees of hydration were produced in anesthetized dogs by constant infusion of dextrose in water at different rates. When water diuresis ensued, and after adequate control periods, vasopressin was infused for 2 1/2 hr. The magnitudes of urine flow and Na excretion varied directly and osmolal urine-to-plasma ratio varied inversely with the degree of hydration. During mild hydration, glomerular filtration rate and osmolal clearance remained practically unchanged, whereas during severe hydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1964
1964
1982
1982

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…min was adequate to prevent the appearance of a water diuresis in a conscious dog. However, it is apparent that in anaesthetized dogs the effectiveness of vasopressin in concentrating the urine is dependent upon the osmolal clearance (Orloff, Wagner & Davidson, 1957) and upon the state of hydration of the animal (Perlmutt, 1962). Recent experiments (Mason & Ledsome, 1971) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…min was adequate to prevent the appearance of a water diuresis in a conscious dog. However, it is apparent that in anaesthetized dogs the effectiveness of vasopressin in concentrating the urine is dependent upon the osmolal clearance (Orloff, Wagner & Davidson, 1957) and upon the state of hydration of the animal (Perlmutt, 1962). Recent experiments (Mason & Ledsome, 1971) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Levitin and associates (2), and Perlmutt (4) obtained their data on dogs during acute water diuresis and within 2 hours after beginning an infusion of vasopressin. Their conclusion seems correct, therefore, that the observed differences in sodium content of medulla and papilla resulted from differences in medullary blood flow.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Jaenike has pre-sented indirect evidence suggesting that vasopressin does not enhance the medullary sequestration of nonurea solute (3). Although other investigators have reported similar studies (4,5), there still is no agreement whether or not vasopressin promotes the medullary sequestration of sodium. The availability of rats with a genetic, apparently absolute, defect for synthesizing vasopressin (6) seemed to present an ideal opportunity for reinvestigating this problem.…”
mentioning
confidence: 99%
“…Numerous investigators have observed that the increase in medullary solute concentration seen in antidiuresis as compared with water diuresis, is a consequence of an increased solute content as well as a reduced water content (2,3,(17)(18)(19)(20)(21). By using graded doses of lysine-vasopressin, Atherton et al (3) further observed that the reduction in free water clearance occurred at a lower dose ofthe hormone than that required to increase medullary solute content.…”
Section: Discussionmentioning
confidence: 99%